Nuclear Energy Generation, Fossil Fuel Price, Energy Mix Generation, Economic Growth, FDI Inflow and CO2 Emission: A Case Study on Developed and Developing Countries in the Asia Pacific Region - Adi, Tri Wahyu; Pawenary, Pawenary; Prabowo, Eri (International Journal of Energy Economics and Policy, 2023)
The net-zero scenario by 2050 (NZE) is a normative scenario that sets the stage for the global energy sector to reach net-zero emissions by 2050. This research aims to explore nuclear energy generation as a potential technological change in a future power generation base load, the factors that are affected and the effects on economic growth, FDI inflow, and CO2 emission in developed and developing countries in the Asia Pacific. The empirical analysis uses time-series data of nuclear energy generation, fossil fuel price, energy mix generation, economic growth, FDI inflow, and CO2 emission in the period 2001 – 2021. The inferential statistical method used to analyse in this research is a component-based using SmartPLS 3.2.9. This research find that Fossil fuel prices have no significant positive effect on nuclear energy generation in developed countries, and the opposite in developing countries, while a negative not significant effect on CO2 emission in both developed and developing countries, with a positive significant effect on economic growth in developed countries and the opposite in developing countries, with a negative significant effect on FDI inflow in developed countries and the opposite in developing countries, with a negative not significant effect on energy mix generation in developed countries and the opposite in developing countries. Nuclear energy generation has a negative not significant effect on energy mix generation in developed countries and the opposite in developing countries, with a negative not significant effect on economic growth in developed countries and the opposite in developing countries, with a positive not significant effect on FDI inflow in developed countries and the opposite in developing countries, with a positive significant effect on CO2 emission in developed countries and the opposite in developing countries. The energy mix generation find has a negative significant effect on economic growth in developed countries and the opposite in developing countries, with a positive significant effect on FDI Inflow and CO2 emission in both developed and developing countries. Economic growth has a negative not significant effect on CO2 emission in both developed and developing countries. FDI inflow has a negative significant effect on CO2 emission in developed countries and the opposite in developing countries.